P082/O24 Sclerostin deficiency affects RANKL-mediated osteoclast differentiation. (March 2019) - Intemann, J; Wehmeyer, C; de Gorter, DJ; Kracke, V; Paruzel, P; Kramer, I; Kneissel, M; Pap, T; Dankbar, B
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: Sclerostin is a Wnt inhibitor and has anti-anabolic effects on bone formation by negatively regulating osteoblast differentiation. Sclerostin loss-of-function leads to a higher bone mass and bone strength. Therefore, inhibition of sclerostin is currently considered as a promising treatment for osteoporosis. Surprisingly, in a TNFα-dependent arthritis mouse model (hTNFtg) the genetic deficiency of sclerostin caused a deterioration of disease severity. hTNFtg mice lacking sclerostin displayed enhanced and bone erosion associated with an elevated number of osteoclasts within the joint. Objectives: In order to understand the underlying mechanisms, we aimed to investigate the direct and indirect impact of sclerostin on osteoclast differentiation and bone erosion in arthritis. Methods: Sclerostin knockout ( sost -/- ) mice were crossbred with hTNFtg mice to obtain sost -/- /hTNFtg mice, from which synovial fibroblasts (SF) were isolated. Cocultures of synovial fibroblasts and green fluorescent protein (GFP + ) bone marrow-derived macrophages (BMM) were performed and osteoclastogenesis was analysed. Receptor activator of NF-kB ligand (RANKL) and macrophage colony stimulating factor (MCSF) expression was measured by ELISA and IL-1a expression by Western Blot. Viability of osteoclasts precursors was measured by MTT Assay. Results: In cocultures of SF and GFP + BMM, osteoclast formation was enhanced by sost -/- /hTNFtg SF compared to hTNFtg SF. Expression of RANKL and MCSF, two crucial factors for osteoclast differentiation, was not different between the genotypes. Interestingly, stimulation of wildtype BMM with conditioned media (CM) from hTNFtg or sost -/- /hTNFtg synovial fibroblasts showed no TRAP + cells at all. However, CM supplemented with RANKL lead to an elevated number of osteoclasts using sost -/- /hTNFtg CM compared to hTNFtg CM, pointing to a secreted factor promoting osteoclast development. In this regard, the osteogenic factor IL-1α, was higher expressed in sost - /- /hTNFtg SF than in hTNFtg SF. Moreover, the treatment of cocultures with recombinant sclerostin lead to a decreased number of osteoclasts in both genotypes. Accordingly, sclerostin inhibited osteoclastogenesis in monocultures when administered in the pre-differentiation phase, whereas no effect was observed in the differentiation phase, indicating an inhibitory effect of sclerostin mainly on osteoclast precursors. Conclusions: Sclerostin deficiency in hTNFtg SF promotes RANKL-mediated osteoclast differentiation, which is likely dependent on the inhibitory effect of sclerostin itself and/or on the promoting effect of higher levels of IL-1α. Disclosure of Interest: None declared.